Biosynthesis and characterization of deuterated chitosan in filamentous fungus and yeast. (1st April 2021) - Yuan, Yue; Li, Hui; Leite, Wellington; Zhang, Qiu; Bonnesen, Peter V.; Labbé, Jessy L.; Weiss, Kevin L.; Pingali, Sai Venkatesh; Hong, Kunlun; Urban, Volker S.; Salmon, Sonja; O'Neill, Hugh
Highlights: Deuterated chitosan was produced from the filamentous fungus Rhizopus oryzae . All non-exchangeable hydrogens were substituted with deuterium except C2 by NMR. SANS shows that deuteration does not change chitosan structure. This is a new approach to produce deuterated chitosan for studies of biocomposites. Abstract: Deuterated chitosan was produced from the filamentous fungus Rhizopus oryzae, cultivated with deuterated glucose in H2 O medium, without the need for conventional chemical deacetylation. After extraction and purification, the chemical composition and structure were determined by Fourier-transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), and small-angle neutron scattering (SANS). 13 C NMR experiments provided additional information about the position of the deuterons in the glucoseamine backbone. The NMR spectra indicated that the deuterium incorporation at the non-exchangeable hydrogen positions of the aminoglucopyranosyl ring in the C3 – C5 positions was at least 60–80 %. However, the C2 position was deuterated at a much lower level (6%). Also, SANS showed that the structure of deuterated chitosan was very similar compared to the non-deuterated counterpart. The most abundant radii of the protiated and deuterated chitosan fibers were 54 Å and 60 Å, respectively, but there is a broader distribution of fiber radii in the protiated chitosan sample. The highly deuterated, soluble fungal chitosan described here can be used as a model material for studying chitosan-enzyme complexes for future neutron scattering studies. Because the physical behavior of non-deuterated fungal chitosan mimicked that of shrimp shell chitosan, the methods presented here represent a new approach to producing a high quality deuterated non-animal-derived aminopolysaccharide for studying the structure-function association of biocomposite materials in drug delivery, tissue engineering and other bioactive chitosan-based composites.